Gracie Harris is under construction : a novel - Hash, Kate (Dutton, PRH, 2025)
"In this resplendent debut novel, a beautiful love story unfolds for tenderhearted Gracie Harris-a mom of two and recent widow-as she navigates the unexpected curveballs that adulthood throws and takes her second chance to find love"-- Provided by publisher.